2x-(3x-6)=5

Simple and best practice solution for 2x-(3x-6)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(3x-6)=5 equation:


Simplifying
2x + -1(3x + -6) = 5

Reorder the terms:
2x + -1(-6 + 3x) = 5
2x + (-6 * -1 + 3x * -1) = 5
2x + (6 + -3x) = 5

Reorder the terms:
6 + 2x + -3x = 5

Combine like terms: 2x + -3x = -1x
6 + -1x = 5

Solving
6 + -1x = 5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1x = 5 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = 5 + -6
-1x = 5 + -6

Combine like terms: 5 + -6 = -1
-1x = -1

Divide each side by '-1'.
x = 1

Simplifying
x = 1

See similar equations:

| 2f(x)=7x-5 | | 8x=6x+2x | | 4x+7=.5(8x+12)+1 | | 3/20p=5 | | 0.4x-0.3x+0.4x=2 | | 144+16x=x | | 1/3j=9j | | -5(v+2)+2v+6=6v+10 | | 2v=6v-8 | | -9w=-8-8w | | b-4.7=3.5 | | ∞/∞ | | 11x+-6y=3 | | ln(8)-5ln(2)=ln(x) | | Y=-9x^2-18x-1 | | 5-5x-10=9+2x-7 | | 3q-10=10-7q | | B/3-7=-7 | | (-7,9);m=4/5 | | 5(x+7)=3(x-(8-x)) | | -5m-9+m=-5 | | 550+12=22 | | -7+4(n-1)=-5(-n+5)-8n | | 550+22=12 | | 2/3-x/4=1/13 | | 12(3x-1)=9(3x+1)+24 | | 5/6x-15=10 | | -ln(1/3)=ln(x) | | 16/25-u/5 | | (10x^2+4)=-35 | | 0.27(10000)-0.02x=0.08(x+10000) | | -p/10-3=5 |

Equations solver categories